Pelatihan Penyusunan Buku Ajar dengan Bantuan Generative Artificial Intelligence - Sholihan; Masruhen; Khofifuddin; Ansharuddin (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2026)
Digital transformation and the development of Generative Artificial Intelligence (GenAI) provide opportunities for lecturers to improve the efficiency and quality of instructional material development. However, its use remains challenged by limited AI literacy, pedagogical competence, evaluation of AI-generated outputs, and academic ethics. This community service activity aimed to improve the competence of lecturers at Institut Agama Islam Hasan Jufri Bawean in using GenAI critically, pedagogically, ethically, and productively for textbook development. The activity was conducted on May 16, 2026, involving 20 lecturers through a participatory training and practice-based mentoring approach. The stages included needs identification and a pre-test, instructional sessions and demonstrations, hands-on textbook development, mentoring, and a post-test. The training covered GenAI orientation, prompt engineering, AI ethics, information verification, and textbook design. Data were analyzed descriptively by comparing participants’ competencies before and after the training. The results showed an increase in lecturers reaching the target competency category from 7 lecturers (35%) to 15 lecturers (75%), representing a 40-percentage-point increase. Five lecturers (25%) still required further development. The findings indicate that practice-based training can strengthen lecturers’ ability to integrate GenAI into textbook development while maintaining academic responsibility for content, pedagogical quality, and ethical use.